최소 필요열량 기준 자급률 산정 - 최지현 (한국농촌경제연구원, 2004)
Objective of this study is to define food self-sufficiency rate based on minimum dietary reference intakes(MDRI)_for energy. The result showed that minimum dietary reference calories will be 1,250～1,500Kcal. For food self sufficiency based on MDRI, In 2020, rice production will be 4,345～5,105 thousand metric tons. Paddy area will be 420～489thousand ha will be needed for rice and total agricultural land will be 960～1,050 thousand ha. Self sufficiency rate for protein and calcium will be 70%, which exist a unbalance between nutrients.
Keywords: 열량